Development, evaluation and application of a simulation model of a sprinter during the first stance phase - Bezodis, N.; Salo, A.; Trewartha, G. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
This study aimed to investigate how alterations in kinematics at touchdown could improve the performance of an international-level sprinter during the first stance phase of a sprint. A seven-segment angle-driven simulation model was developed, and evaluation against empirical data revealed the model matched reality to within a mean value of 5.2%. A series of simulations altering the horizontal distance between the stance foot and the CM at touchdown were undertaken. By positioning the foot slightly further behind the CM, performance (external power) was improved due to favourable increases in horizontal force production and only small increases in stance duration. However, continuing to increase this distance between the foot and the CM led to decreased performance due to an inability to generate sufficient force despite continued increases in stance duration.